Studi Literatur : Hubungan Asupan Folat Dan Zink Dengan Kejadian Anemia Ibu Hamil - Annisa Mudrika; Novriani Tarigan; Sudana Fatahillah Pasaribu (Lembaga Pengembangan Kinerja Dosen, 2023)
Anaemia in pregnancy is still a problem in the world, with a global prevalence of (40%), The main cause of anaemia is a lack of micronutrients that play a role in the formation of hemoglobin. The Centers for Disease Control and Prevention (CDC), in 2015 revealed that around 2 billions people in the world suffered from micronutrient deficiencies. Pregnant women are susceptible to micronutrient deficiencies because during pregnancy the fetus grows in the womb, the micronutrients needed during pregnancy include folic acid and zinc. This study aims to obtain a theoretical basis that can support problem solving, based on this objective the researcher chose the method of literature review. Based on the results of the study, it was found that there was a correlation between folic acid intake and the incidence of anemia in pregnant women with each p < 0.05. While the articles discussing zinc intake 50% of them revealed that there was a relationship between zinc intake and the incidence of anemia in pregnant women, while the other 50% revealed that there was no significant relationship between zinc intake and the incidence of anaemia in pregnant women. Excess zinc is one of the causes of anemia. Apart from that, folic acid and zinc have an important role in the synthesis of protein which is one of the substances that form red blood cells. Zinc is a cofactor of the methyl transferase enzyme, where this enzyme is needed in the metabolism of folic acid which will later play a role in a series of protein synthesis processes.